Perfil de pesquisa dos departamentos da Faculdade de Engenharia do Campus de Guaratinguetá - Carboneri, Thiago Cabral [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
To know the profile of research of each Department of Education is of utmost importance for future actions of improvements. This type of study must be made continuously of form to evaluate Departments´ trends as well as the College´s as a whole, besides stimulating the activities of research and formation of human resources of the Departments. In this work is quantified activity of orientation and research of the Departments of the College of Engineering of Guaratinguetá - UNESP, through national and international publications in periodic, congresses and supervisions of graduation works, masters, doctoral, post doctoral, and scientific initiation, in a period five years (2007 through 2012). For balance of points to the considered issues, a criterion based on the CAPES qualification of periodic has been assumed. On the basis of the results of this work, has been observed enormous differences and particularities between the seven analyzed Departments of Education. In a general way, some Departments presented good performance in the three criteria, whereas others obtained a good performance in only one of them. The Department of Materials and Technology was the only one in which 25% of the professors obtained maximum note for the publication in periodic, while in the Departments of Civil, Electric Engineering and Mechanics 75% of the professors did not reach sufficient punctuation in order to equal a publication in periodic with B2 extract

Conhecer o perfil de pesquisa de cada Departamento de Ensino é de suma importância para futuras ações de melhorias. Esse tipo de estudo deve ser feito continuamente de forma a avaliar tendências tanto dos Departamentos quanto da Faculdade como um todo, bem como estimular as atividades de pesquisa e formação de recursos humanos dos Departamentos. Neste trabalho quantifica-se a atividade de orientação e pesquisa dos Departamentos da Faculdade de Engenharia do Campus de Guaratinguetá – UNESP, através de publicações em periódicos, congressos nacionais e internacionais e orientações de trabalhos de graduação, mestrados, doutorados, pós-doutorado e iniciação científica, em um período de cinco anos (2007 a 2012). Para ponderação de pontos aos quesitos considerados, foi assumido um critério baseado na qualificação de periódicos da CAPES. Com base nos resultados deste trabalho, observaram-se diferenças e particularidades entre os sete Departamentos de Ensino analisados. De modo geral, alguns Departamentos apresentaram bom desempenho nos três quesitos, ao passo que outros conseguiram um bom desempenho em apenas um dos quesitos. O Departamento de Materiais e Tecnologia foi aquele no qual 25% dos docentes conseguiram nota máxima para a publicação em periódicos, enquanto que nos Departamentos de Engenharia Civil, Elétrica e Mecânica mais de 75% dos docentes não obtiveram pontuação equivalente a uma publicação em periódico com extrato B2
Keywords: Universidade Estadual Paulista Júlio de Mesquita Filho; Pesquisa; Orientação